Extracellular α-synuclein leads to microtubule destabilization via GSK-3β-dependent Tau phosphorylation in PC12 cells. - Magdalena Gąssowska; Grzegorz A Czapski; Beata Pająk; Magdalena Cieślik; Anna M Lenkiewicz; Agata Adamczyk (PLoS ONE, 2014)
α-Synuclein (ASN) plays an important role in pathogenesis of Parkinson's disease (PD) and other neurodegenerative disorders. Novel and most interesting data showed elevated tauopathy in PD and suggested relationship between ASN and Tau protein. However, the mechanism of ASN-evoked Tau protein modification is not fully elucidated. In this study we investigated the role of extracellular ASN in Tau hyperphosphorylation in rat pheochromocytoma (PC12) cells and the involvement of glycogen synthase kinase-3β (GSK-3β) and cyclin-dependent kinase 5 (CDK5) in ASN-dependent Tau modification. Our results indicated that exogenously added ASN increases Tau phosphorylation at Ser396. Accordingly, the GSK-3β inhibitor (SB-216763) prevented ASN-evoked Tau hyperphosphorylation, but the CDK5 inhibitor had no effect. Moreover, western blot analysis showed that ASN affected GSK-3β via increasing of protein level and activation of this enzyme. GSK-3β activity evaluated by its phosphorylation status assay showed that ASN significantly increased the phosphorylation of this enzyme at Tyr216 with parallel decrease in phosphorylation at Ser9, indicative of stimulation of GSK-3β activity. Moreover, the effect of ASN on microtubule (MT) destabilization and cell death with simultaneous the involvement of GSK-3β in these processes were analyzed. ASN treatment increased the amount of free tubulin and concomitantly reduced the amount of polymerized tubulin and SB-216763 suppressed these ASN-induced changes in tubulin, indicating that GSK-3β is involved in ASN-evoked MT destabilization. ASN-induced apoptotic processes lead to decrease in PC12 cells viability and SB-216763 protected those cells against ASN-evoked cytotoxicity. Concluding, extracellular ASN is involved in GSK-3β-dependent Tau hyperphosphorylation, which leads to microtubule destabilization. GSK-3β inhibition may be an effective strategy for protecting against ASN-induced cytotoxicity.